Network Pharmacology Analysis of Orally Bioavailable SARS-CoV-2 Protease Inhibitor Shows Synergistic Targets to Improve Clinical Efficacy - Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports)
Introduction: Orally bioavailable SARS-CoV-2 antiviral drugs will significantly improve the clinical management of the disease. PF07321332 (PF32) one such orally bioavailable SARS- CoV-2 protease inhibitor which can be helpful to prevent viral replication in the host. Materials and Methods: Hence this study evaluated the network pharmacology of PF32 using established methods to predict its potential safety and efficacy. Results: PF32 was selective against SARS-CoV-2 proteases without any affinity against SARS-CoV-2 RNA polymerase or its spike protein. While PF32 showed pharmacologically relevant affinity against several targets in human tissues. The target profiling of PF32 indicated a fourfold selectivity towards several proteases in human tissues with an affinity (IC50) ranging from 26 to 41 nM. Conclusion: The predicted inhibitory effects of PF32 against both host and viral proteases may have synergistic effects for superior clinical efficacy.
Keywords: Molecular interaction; Protease inhibitor; SARS-CoV-2; Antiviral; Coronavirus